Reflections on the impact of informational asymmetry on goodwill - Costa, Ana Clara Gonçalves Calaça; Rodrigues, Jomar Miranda; Niyama, Jorge Katsumi; Silva, César Augusto Tibúrcio (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This theoretical essay aims to discuss and present the disclosure of informational asymmetry in transactions related to goodwill and their effects on information users. Methodology: A theoretical essay explores the discussions in the academic field concerning transactions and operations involving goodwill. Because of its unique intangible nature, goodwill allows a high level of managerial discretion, as granted by regulations. This situation can create an environment where some agents possess more information in a transaction, due to informational asymmetry. These factors can lead to market issues and even earnings management. Results: The literature analysis identified informational asymmetry in goodwill and its consequences for the institution's stakeholders, such as a lack of knowledge about organizational movements related to this asset and its impact on decision-making. Contributions of the Study: The study contributes to the academic discussion on the specific aspects of goodwill and its impact on accounting. Furthermore, it reveals important discussion topics for a better consolidation of accounting practice.